(untitled) (Collection of scientific works «Modern structures of metal and wood», 2023)
Elements and structures made of wood have repeatedly proven their advantages over analogues made of metal and reinforced concrete. At the same time, materials, parts, elements and structures made of wood need additional experimental and theoretical studies to establish the actual mechanical characteristics of the material. That is, analysis with subsequent modeling of the work of wood as a material from the beginning of loading to its complete destruction. Most of the experimental studies of solid wood were carried out in the so-called "soft" test mode, that is, the work of such material was analyzed only up to a certain point of the ascending branch of the "σ-u" diagram (according to the increase in loads), which did not allow us to accurately study the strength and deformable characteristics on top of this chart, not to mention its descending branch. Since the end of the last century, scientists from different countries began to conduct experimental studies of materials in the so-called "hard mode" (increasing displacements) on modern servo-hydraulic and electromechanical testing machines, which made it possible to build diagrams from the beginning of loading to the complete destruction of the material. The purpose of the work is to develop a theoretical model for the operation of hardwood and coniferous wood under axial compression along the fibers with a short-term load from the beginning of loading to the complete destruction of the material, regardless of the age of the wood and humidity. A generalized model of the actual work of hardwood and coniferous wood under axial compression along the fibers by a short-term load is proposed. Four characteristic areas of wood work were established (two on the ascending branch and two on the descending one). A theoretical definition of the main strength and deformation parameters of the complete wood deformation diagram is proposed. An approximating function has been established - this is a polynomial of the 4th degree, which sufficiently describes the deformation diagram. Methods for determining the critical and limiting deformations of wood, the initial modulus of elasticity and the modulus of deformations are proposed.